A case of 15q11‐q13 duplication syndrome and literature review - Zhuo Fu; Yue‐Xin Jia; Jun‐Xian Fu; Tian‐Xia Li; Jing‐Jing Zhao; Ting Wang; Zhi‐Dong Qiao; Xiao‐Yang Liu; Rong Tang; Ting Lv; Guang‐Lu Yang (Brain and Behavior, 2021)
Abstract Background The chromosomal 15q11‐q13 regions are structurally complex, and their abnormalities are associated with various neuropsychiatric disorders, including autism spectrum disorder (ASD), epilepsy, Angelman syndrome, and Prader–Willi syndrome. Case description A 6‐year‐old child was admitted to the hospital as a result of an “epileptic status” showing ASD, intractable epilepsy, and total developmental retardation. Chromosome gene detection showed repetitive variation in the 15q11‐q13 regions, and the video electroencephalogram was abnormal. Although children are currently given antiepileptic treatment and rehabilitation training, intermittent seizures can still occur. Conclusion The clinical phenotypes of 15q11‐q13 repetitive syndrome are complex, and vary in severity. Children with intractable epilepsy, ASD, and language and motor retardation should be considered to have this syndrome, which requires confirmation by multiplex ligation‐dependent probe amplification and gene detection. These approaches can enable early rehabilitation treatment and improve the patients’ quality of life.